Pesticide Options for Insect, Mite, and Mollusk Management in Commercial Strawberry Production in Florida - James F. Price; Curtis Nagle; Susan E. Webb (EDIS)
Effective management of arthropod and gastropod pests of strawberry is critical to the profitability of the industry and requires that pests be detected in a timely manner through systematic scouting. Appropriate control measures should be applied as conditions warrant. The tables in this 22-page fact sheet list pesticides that are presently available to commercial strawberry producers in Florida and are organized alphabetically by major pest groups. Written by James F. Price, Curtis Nagle, and Susan E. Webb, and published by the UF Department of Entomology and Nematology, April 2013.